Hubungan Pengetahuan dan Persepsi Ibu dengan Kepatuhan dalam Pemberian Imunisasi MR Lanjutan - Eva Hotmaria Simanjuntak; Yunida Turisna Simanjuntak; Roselina Situmorang (Universitas Ngudi waluyo, 2022)
Adherence in administering advanced Measles Rubella (MR) Immunization in the Work Area of the Niaga Kesiangan Health Center is still low. The low compliance in giving advanced Measles Rubella (MR) Immunization in the Work Area of the Naga Kesiangan Health Center is related to the knowledge and perceptions of the mother. This study aims to determine the relationship between knowledge and perceptions of mothers with adherence to the provision of advanced Measles Rubella (MR) immunization in the Work Area of the Puskesmas Naga Kesiangan. This type of research is analytic survey research with cross sectional design. The population in this study were all mothers who have toddlers aged 18-25 months in the working area of the Naga Kesiangan Health Center, totaling 151 people with a sample of 60 people. Collecting data with primary and secondary data and analyzed by statistical test Chi Square with a confidence level of 95%. The results showed that there was a relationship between maternal knowledge and adherence in the provision of advanced Measles Rubella (MR) Immunization in the Puskesmas Naga Kesiangan Work Area and there was a relationship between maternal perception and adherence to advanced Measles Rubella (MR) immunization in the Puskesmas Naga Kesiangan Work Area. It is recommended that mothers in the working area of the Naga Kesiangan Health Center need to increase their knowledge about the provision of further Measles Rubella (MR) immunization by following counseling held by health workers and seeking information about advanced Measles Rubella (MR) immunization and to health workers in the Work Area of the Naga Kesiangan Health Center. improve maternal understanding of continued Measles Rubella (MR) Immunization and improve maternal perceptions in an effort to increase compliance with continued Measles Rubella (MR) immunization.Abstrak Kepatuhan dalam pemberian Imunisasi Measles Rubella (MR) lanjutan di Wilayah Kerja Puskesmas Niaga Kesiangan masih rendah. Rendahnya kepatuhan dalam pemberian Imunisasi Measles Rubella (MR) lanjutan di Wilayah Kerja Puskesmas Naga Kesiangan terkait dengan pengetahuan dan persepsi ibu. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dan persepsi ibu dengan kepatuhan dalam pemberian imunisasi Measles Rubella (MR) lanjutan di Wilayah Kerja Puskesmas Naga Kesiangan. Jenis penelitian yang digunakan adalah penelitian survei analitik dengan desain cross sectional. Populasi dalam penelitian ini adalah seluruh ibu yang memiliki Balita usia 18-25 bulan di wilayah Kerja Puskesmas Naga Kesiangan yang berjumlah 151 orang dengan sampel sebanyak 60 orang, dengan teknik simple random sampling. Pengumpulan data dengan data primer dan sekunder dan dianalisis dengan uji statistik chi Square dengan tingkat kepercayaan 95%. Hasil penelitian menunjukkan bahwa terdapat hubungan pengetahuan ibu dengan kepatuhan dalam pemberian Imunisasi Measles Rubella (MR) lanjutan di Wilayah Kerja Puskesmas Naga Kesiangan dan terdapat hubungan persepsi ibu dengan kepatuhan dalam pemberian Imunisasi Measles Rubella (MR) lanjutan di Wilayah Kerja Puskesmas Naga Kesiangan. Disarankan kepada ibu di Wilayah Kerja Puskesmas Naga Kesiangan perlu meningkatkan pengetahuan tentang pemberian Imunisasi Measles Rubella (MR) lanjutan dengan mengikuti penyuluhan yang diadakan petugas kesehatan dan mencari informasi tentang imunisasi Measles Rubella (MR) lanjutan dan kepada tenaga kesehatan di Wilayah Kerja Puskesmas Naga Kesiangan perlu meningkatkan pemahaman ibu tentang pemberian imunisasi Measles Rubella (MR) lanjutan dan meningkatkan persepsi ibu dalam upaya peningkatan kepatuhan pemberian imunisasi Measles Rubella (MR) lanjutan.